The Impact Of Social Media On Online Consumer Behavior: An Islamic Economic Perspective - Khairul Anwar; Pardi Setiawan; Siti Darma Mar’atus Solihah (Yayasan Abdurrauf Cendekia Nusantara, 2025)
The development of digital technology and social media has changed consumer behavior patterns in online shopping activities. This study aims to examine the impact of social media on Muslim consumer behavior and analyze online consumer behavior from an Islamic economic perspective. This is a library research study with a descriptive qualitative approach. Data was collected through literature studies and analysis of various relevant previous research findings. The results show that online consumers tend to prioritize convenience, speed, competitive prices, and reviews from other users when deciding on a product. Social media plays a significant role as a source of information, a means of promotion, and a shaper of brand perception that influences the interests and purchasing decisions of Muslim consumers. In addition, trust and previous shopping experiences also strengthen consumer loyalty to certain platforms. The behavior of Muslim online consumers is driven by a combination of material and spiritual needs, where they not only seek shopping convenience but also ensure sharia compliance, such as the principles of halal and thayyib, the prohibition of tabzir, avoidance of gharar, and clarity of contracts. This study is expected to contribute to business actors in designing effective digital marketing strategies oriented towards the needs and preferences of Muslim online consumers.